MD&A ON SHARIA STOCK EXISTENCE - Nur Wahyu Ningsih; Ridwansyah Ridwansyah; Ahmad Zuliansyah (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2019)
This study aims to provide empirical evidence regarding stock returns as the impact of Management's Discussion and Analysis disclosure on companies listed in the Jakarta Islamic Index, Indonesia Stock Exchange, in the 2015-2017 period. The motivation behind this research is the absence of research in Indonesia which studies the presentation of MD & A which influences investors' decisions to invest in companies listed in the Jakarta Islamic Index, seen from the company's stock returns. This study used 63 samples. The hypothesis in this study was tested using a partial correlation of simple linear regression. The results showed that there is a positive relationship between MD & A disclosure of stock returns. From the results presented, it is expected that companies listed in the Jakarta Islamic Index can disclose MD & A fully and openly so that they can attract investors to invest. With the increase in stock returns to the value of the company, the existence of Islamic stocks can be increased. Therefore, Indonesia is expected not only to become a large market and place for the Muslim population but also to empower its people through the halal industry including the existence of Islamic stocks in Indonesia.